1.8k views
3 votes
Factor the binomial 9t^2 -4 = (i uploaded the screenshot 2 or 3 times now

Factor the binomial 9t^2 -4 = (i uploaded the screenshot 2 or 3 times now-example-1

1 Answer

5 votes

The given binomial is

9t^2 - 4

Recall,

4 = 2^2

9 = 3^2

Thus, it can be rewritten as

3^2t^2 - 2^2

(3t)^2 - 2^2

We would apply the difference of two squares whcih is expressed as

(A^2 - B^2) = (A + B)(A - B)

By comparing both expressions,

A = 3t and B = 2

Thus, the factored form of the binomial is

(3t + 2)(3t - 2)

User CL So
by
5.4k points